Microarcsecond structure of an AGN Jet via Interstellar Scintillation. Issue Volume 10:Issue S313(2014) (24th March 2015) - Bignall, Hayley; Macquart, Jean-Pierre; Godfrey, Leith; Hodgson, Jeffrey; Jauncey, David
Abstract: We have used the broadband backend available at the ATCA to study the fast interstellar scintillation (ISS) of quasar PKS 1257–326, resolving the core shift as a function of frequency on scales less than 10 microarcseconds. In this short paper we discuss the jet direction implied from the microarcsecond-scale core shift in PKS 1257–326.